Update on Critical Issues on Infant and Neonatal Care 2020
DOI: 10.5772/intechopen.89611
|View full text |Cite
|
Sign up to set email alerts
|

Universal Screening for Congenital CMV Infection

Abstract: Congenital cytomegalovirus (CMV) infection is an important public health problem. It is a leading cause of disability in children. Congenitally infected neonates often appear asymptomatic at birth or have nonspecific symptoms. An early diagnosis and subsequent early antiviral therapy associated to nonpharmacological therapy (e.g., hearing rehabilitation, speech-language therapy, and cochlear implants) can reduce long-term disability. Much research has been done in this field, but further studies are still nece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 43 publications
0
5
0
1
Order By: Relevance
“…A high incidence of congenital CMV infection in preterm infants has been previously reported: congenital infection was identified in 8 (2.4%) of 342 (≤31 weeks gestation and birth weight ≤1500 g) in a study carried out in Spain and in 10 (3%) of 329 preterm infants (<37 weeks gestation) in a study carried out in Italy 37,38 . As a result, universal screening for congenital CMV infection in very preterm infants is recommended by several authors 32,33,42 . In contrast, other studies have reported the incidence of congenital CMV infection to be similar, or even lower, in preterm infants compared to term infants 34,39,43 .…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…A high incidence of congenital CMV infection in preterm infants has been previously reported: congenital infection was identified in 8 (2.4%) of 342 (≤31 weeks gestation and birth weight ≤1500 g) in a study carried out in Spain and in 10 (3%) of 329 preterm infants (<37 weeks gestation) in a study carried out in Italy 37,38 . As a result, universal screening for congenital CMV infection in very preterm infants is recommended by several authors 32,33,42 . In contrast, other studies have reported the incidence of congenital CMV infection to be similar, or even lower, in preterm infants compared to term infants 34,39,43 .…”
Section: Discussionmentioning
confidence: 95%
“…37,38 As a result, universal screening for congenital CMV infection in very preterm infants is recommended by several authors. 32,33,42 In contrast, other studies have reported the incidence of congenital CMV infection to be similar, or even lower, in preterm infants compared to term infants. 34,39,43 As such, further research is required to determine if the incidence of congenital CMV infection is greater in preterm infants.…”
Section: Discussionmentioning
confidence: 96%
“…In turn, increased awareness encourages parent queries and drives more providers to perform cCMV screening despite absent or limited CPGs. Participants similarly emphasized the documented benefits of early interventions on the long-term outcomes of hearing loss, developmental delay, and other conditions with variable causes, including cCMV infection [ 35 , 36 ]. Evidence of these benefits regardless of etiology provides rationale for cCMV screening and may transform formal CPGs and/or local clinical practice patterns.…”
Section: Resultsmentioning
confidence: 99%
“…En suma, un programa de cribado universal de infección por CMVc permitiría evaluar oportunamente al RN, considerar el tratamiento y realizar un seguimiento activo a largo plazo, agregados a potenciales beneficios sociales y en salud pública por disminución de carga y costo por discapacidad 58 . Los estudios de costo-beneficio realizados, tanto para cribado universal como en grupos de riesgo, han mostrado utilidad 59 ; sin embargo, en lugares con recursos limitados, el cribado universal pareciera ser impracticable por ahora, sobre todo porque el tratamiento del RN asintomático sigue siendo controversial. En nuestra realidad se podría recomendar, al menos, el cribado en grupos de riesgo: RN que refieren el estudio auditivo al nacer, hijos de madre con infección por VIH, prematuros extremos, PEG severos y en todo aquel que se sospecha por antecedentes prenatales o manifestaciones clínicas al nacer.…”
Section: Discussionunclassified